Model of Learning Objects Exchange between LCMS Platforms through Intelligent Agents1 - Gaona García, Paulo Alonso (2015)
Currently, there are a variety of digital resources hosted on the Internet, based on access points such as digital libraries and repositories. The majority of strategies to store information are used by specialized documentation centers, academic institutions, and databases of regional development policies. These entities have been directing their efforts to improve the access over a collection of digital resources for academic and professional purposes. There is still a lot of educational material that is hosted on content management tools known as Learning Content Management System (LCMS); however, those tools do not perform the corresponding indexing of digital resources for the use of repositories. In fact, this requirement reduces the access to digital resources even from the inside of each academic institution, losing coverage and recognition in other learning environments. Moreover, this factor also limits the enrichment and linking of related academic material. Then, strategies such as Linked Data cannot be extensively used to share digital resources. Therefore, this article aims to devise an indexing strategy to manage digital resources hosted in different LCMS by defining services that facilitate the exchange of digital resources and their reuse. Case Study: Efront and Moodle platforms.